2010
DOI: 10.1177/039139881003300603
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two Subpopulations of the PICM-19 Porcine Liver Stem Cell Line for use in Cell-Based Extracorporeal Liver Assistance Devices

Abstract: Two cell lines, PICM-19H and PICM-19B, were derived from the bipotent PICM-19 pig liver stem cell line and assessed for their potential application in artificial liver devices (ALD). The study included assessments of growth rate and cell density in culture, morphological features, serum protein production, gamma-glutamyltranspeptidase (GGT) activity and hepatocyte detoxification functions, i.e., inducible P450 activity, ammonia clearance, and urea production. The PICM-19H cell line was derived by temperature s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Studies using a substrate of living, but non-dividing "feeder cells" such as rat liver epithelial cell lines (Guguen-Guillouzo et al 1983), 3T3 cells (Joplin et al 1989;Kuri-Harcuch and Mendoza-Figueroa 1989), and human diploid fibroblasts (Michalopoulos et al 1979) have also demonstrated long-term in vitro maintenance of hepatocyte morphology and function. Our laboratory has previously demonstrated that feeder cells prepared from the STO mouse embryonic fibroblasts cell line were capable of maintaining replicating cultures of pig embryonic stem cellderived, and fetus-derived, porcine hepatocytes and cholangiocytes, the latter spontaneously self-organizing into multicellular ductal structures that displayed in vivo-like responses (Talbot et al 1994a(Talbot et al , b, 1996(Talbot et al , 2002(Talbot et al , 2010aWillard et al 2009). Thus, mitotically inactivated STO feeder cells may be a suitable substrate for the primary culture of cells from the livers of young or young-adult pigs.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using a substrate of living, but non-dividing "feeder cells" such as rat liver epithelial cell lines (Guguen-Guillouzo et al 1983), 3T3 cells (Joplin et al 1989;Kuri-Harcuch and Mendoza-Figueroa 1989), and human diploid fibroblasts (Michalopoulos et al 1979) have also demonstrated long-term in vitro maintenance of hepatocyte morphology and function. Our laboratory has previously demonstrated that feeder cells prepared from the STO mouse embryonic fibroblasts cell line were capable of maintaining replicating cultures of pig embryonic stem cellderived, and fetus-derived, porcine hepatocytes and cholangiocytes, the latter spontaneously self-organizing into multicellular ductal structures that displayed in vivo-like responses (Talbot et al 1994a(Talbot et al , b, 1996(Talbot et al , 2002(Talbot et al , 2010aWillard et al 2009). Thus, mitotically inactivated STO feeder cells may be a suitable substrate for the primary culture of cells from the livers of young or young-adult pigs.…”
Section: Introductionmentioning
confidence: 99%
“…For clonal, spontaneous in vitro differentiation, the giPSC cell lines were passaged onto STO feeder cells prepared as previously described (Talbot et al, ), except that the STO feeder cells were seeded at 2.5 × 10 4 cells/cm 2 in T12.5 tissue‐culture flasks (BD Biosciences, San Jose, CA). The giPSC cells were plated in 10% DMEM at clonal density (i.e., 100 cells per T12.5 flask).…”
Section: Methodsmentioning
confidence: 99%
“…Two‐dimensional electrophoretic analysis of the serum‐free, conditioned medium from giPSC B5‐derived yolk‐sac endoderm cells was performed as previously described (Talbot et al, ). Briefly, a T12.5 flask of the cells was washed four times with serum‐free medium (DMEM) and re‐fed with 2 ml of serum‐free medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although considerable expertise has been gained in the use of xenogenic hepatocyte-driven BAL (9)(10)(11)(12), serious concerns exist about their use. One of the main recognized disadvantages is immunological rejection.…”
mentioning
confidence: 99%